Plasmapheresis in Neonatal Lupus - Mark Sharobim; Angelica S. J. Scribner; William N. Rose (Rheumato, 2022)
About 2% of mothers with Sjögren’s syndrome and about 1% of mothers with systemic lupus erythematosus deliver a baby with a congenital heart block (CHB). This is thought to be as a result of the maternal autoantibodies that cross the placenta and cause congenital lupus in the fetus/neonate. Among patients with a 2nd or 3rd degree atrioventricular block, the mortality rate in the neonatal period is about 10%, and most neonates who survive require a pacemaker into adulthood. Despite the compelling mortality and morbidity, the data on the optimal preventive treatments are meager and not well-established. In addition to pharmaceutical therapy, one potentially effective therapy is plasmapheresis. Plasmapheresis is safe in pregnancy, well tolerated, and is effective in removing the offending substances in the serum which may cause disease. We review this literature, in order to educate the reader and to motivate interest in studying this condition in the future.